Peptide inhibitors of the anaphase promoting-complex that cause sensitivity to microtubule poison. - Scott C Schuyler; Yueh-Fu Olivia Wu; Hsin-Yu Chen; Yi-Shan Ding; Chia-Jung Lin; Yu-Ting Chu; Ting-Chun Chen; Louis Liao; Wei-Wei Tsai; Anna Huang; Lin-Ing Wang; Ting-Wei Liao; et al. (PLoS ONE)
There is an interest in identifying Anaphase Promoting-Complex/Cyclosome (APC/C) inhibitors that lead to sensitivity to microtubule poisons as a strategy for targeting cancer cells. Using budding yeast Saccharomyces cerevisiae, peptides derived from the Mitotic Arrest Deficient 2 (Mad2)-binding motif of Cell Division Cycle 20 (Cdc20) were observed to inhibit both Cdc20- and CDC20 Homology 1 (Cdh1)-dependent APC/C activity. Over expression of peptides in vivo led to sensitivity to a microtubule poison and, in a recovery from a microtubule poison arrest, delayed degradation of yeast Securin protein Precocious Dissociation of Sisters 1 (Pds1). Peptides with mutations in the Cdc20 activating KILR-motif still bound APC/C, but lost the ability to inhibit APC/C in vitro and lost the ability to induce sensitivity to a microtubule poison in vivo. Thus, an APC/C binding and activation motif that promotes mitotic progression, namely the Cdc20 KILR-motif, can also function as an APC/C inhibitor when present in excess. Another activator for mitotic progression after recovery from microtubule poison is p31comet, where a yeast predicted open-reading frame YBR296C-A encoding a 39 amino acid predicted protein was identified by homology to p31comet, and named Tiny Yeast Comet 1 (TYC1). Tyc1 over expression resulted in sensitivity to microtubule poison. Tyc1 inhibited both APC/CCdc20 and APC/CCdh1 activities in vitro and bound to APC/C. A homologous peptide derived from human p31comet bound to and inhibited yeast APC/C demonstrating evolutionary retention of these biochemical activities. Cdc20 Mad2-binding motif peptides and Tyc1 disrupted the ability of the co-factors Cdc20 and Cdh1 to bind to APC/C, and co-over expression of both together in vivo resulted in an increased sensitivity to microtubule poison. We hypothesize that Cdc20 Mad2-binding motif peptides, Tyc1 and human hp31 peptide can serve as novel molecular tools for investigating APC/C inhibition that leads to sensitivity to microtubule poison in vivo.